Pengaruh Transformational Leadership dan Perceived Organizational Support terhadap Job Performance: Peran Mediasi Work Engagement - Wahid Mirza Prabowo; Muafi Muafi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
The purpose of this study was to examine and analyze the influence of transformational leadership and perceived organizational support on job performance mediated by work engagement on employees of Data Center and Information System of the Ministry of Agriculture in Jakarta, Indonesia. Respondents in this study are 75 employees of the Data Center and Information System of the Ministry of Agriculture. The analytical test tool used is the SMART PLS software with SEM (Structural Equation Modeling) analysis method.The result of this study indicates that transformational leadership has a positive effect on work engagement, perceived organizational support has a positive effect on work engagement, work engagement has a positive effect on job performance, transformational leadership has a positive effect on job performance, perceived organizational support has a positive effect on job performance, transformational support has a positive effect on job performance mediated by work engagement, and perceived organizational support has a positive effect on job performance mediated by work engagement.